Analysis of the Operating Energy Variables Involved in Mechanized Khoa Production - Patel A. D; Patel S. I.; Patel S. M; R. B. Modi (Archives of Current Research International, 2024)
Significant portion of the total milk production of India has been utilized for the manufacture of the Traditional Indian Dairy Products (TIDP). Khoa based products were traditionally produced in the Indian sub-continent since ancient times. Khoa produced by the mechanized methods can overcome the demerits of traditional manufacturing methods like insufficient use of energy, poor hygiene and sanitation, non-uniform product quality, etc. In the present study, steam jacketed open type hemispherical kettle equipped with spring loaded Teflon edged scraper blade assembly was utilized for the mechanized production of khoa. A standardized mixed milk having (6.0±0.1%) fat and (9.0±0.2%) SNF, was evaporated to the different level of concentration using a batch type vacuum pan. The performance of the mechanized manufacture of khoa was evaluated at different steam pressures (P1= 98.06 kPa, P2=147.1 kPa, P3=171.61 kPa), scraper speed (R1=0.67rps), and different level of milk concentration (C1=35 %TS, C2=40 %TS, C3=45 %TS) for first stage. During the second stage, effect of operating variables on process mechanization were evaluated at different steam pressures (S1= 49.03 kPa and S2= 78.45 kPa) and scraper speed (R2=0.33rps). The primary objective of present study is to carry out thermal and electrical energy analysis associated with mechanized khoa production, which has a significant role in process optimization, scale-up of the operation and to design and fabricate the mechanized system. The overall heat transfer coefficients (U-values) of the mechanized system obtained at various processing parameters ranged from 156.87 to 234.16 W/m2K during khoa manufacturing. The treatment C1 P1 S2 gave the highest U-values for sensible and latent heating. The mean U-values of sensible heating and latent heating were increased with an increase in steam pressure during khoa making in the mechanized system. The mean value of specific steam consumption (kg steam/kg water evaporated) for the optimized operating conditions was 1.950 (kg steam/kg water evaporated) for manufacture of khoa in mechanized system. The total heat losses of mechanized system during manufacture of khoa was 17.15 to 28.02 % at different operating conditions studied. The mean values of electrical power consumption ranged from 141 to 203 Wh under different operating conditions. Considering the energy consumption data, we can narrate that existing system is energy efficient with lower electrical energy consumption and can reduce the labour cost due to mechanization.